Empower employees to step away, with the greater goal of enhancing leadership. Issue 10 (24th January 2018) - Skipworth, Stan
Abstract : With current technology, content and functions including, news, sports scores, sending and receiving documents, accessibility by phone — even music, television, and movies — is instantly available. The descriptions of the very devices we choose to access these various information sources and systems highlight their speed: A computer with significantly greater memory and an enhanced processor and faster internet service create the expectation we are capable of handling greater amounts of data, will have a more enjoyable online experience, and will be more effective at work.